The complete chloroplast genome of Actinidia rubus (Actinidiaceae). Issue 1 (2nd January 2020) - Xu, Yu-Sheng; Zhang, Cheng-Gui; Chen, Jun-Tong; Li, Li-Juan; Liao, Chuan-Jiang; Lv, Zhen-Yu; Jiang, Zhi-Lin
Abstract: A complete chloroplast genome of Actinidia rubus, an endemic shrub in China, was sequenced and identified. The length of genome is 156, 573 bp, and the GC content is 37.3%. This genome contains a large single copy (LSC; 88, 473 bp) region, a small single copy (SSC; 20, 492) region, a pair of inverted repeat (IR; 23, 804) regions. A total of 113 unique genes were identified, including 78 protein-coding genes, 31 tRNA genes and 4 rRNA genes. The phylogenetic analysis based on complete chloroplast genome of 10 species showed that Actintdia eriantha was sister to A. rubus .